Etika Animalitas - Borrong, Robert Patannang (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2019)
AbstractWhy animal ethics? The importance of animal ethics for the Indonesian public is to respond to the extinction threat of some animal species in Indonesia, like Tiger in Sumatera, Orang Utan in Kalimantan, Anoa in Sulawesi, and Cendrawasih in Papua. The way humans consume animals is often cruel, causing pain and suffering on the part of the animals. Such an attitude indicates the lack of moral standing in animal sphere. Philosophicallyand theologically, animal has sentience and intrinsic values which with humans have to recognise as the moral standard for animal.Using the theological-ethical concept that human being was created in the image of God, which means that they are not only endowed with senses but also the intellect to make them moral standing creature, this article points to the capacity as well as responsibility of humans to the environment, specifically to the animal world (animalities). As such, animals have to be regarded as having moral standing in the context of human beings’moral attitude and treat. Animals have to be respected and loved morally because they have sense, sentience and intrinsic value. Animals have feeling of pleasure and suffering which with human beings must honor and make as a moral standard. Like human beings, animals have the right to enjoy contentment and to be protected as the good creatures created by God. Although consuming animals can be considered part of natural order and natural recycle, animals have the right to enjoy liberation and prosperity during they are living, and to be avoided from suffering. In this sense, life and death must be accepted in balance. As a conclusion, in relating to animals, humans should demonstrate the virtues of respect, love, justice, and restrained attitudes. Animal ethics, thus, concerns with the sustainability of the peace and welfare of the whole creation on the planet earth. AbstrakMengapa etika animalitas diperlukan? Bagi publik Indonesia, etika animalitas sangat penting karena ada banyak hewan/binatang di Indonesia terancam punah akibat perburuan yang tidak mempertimbangkan etika, antara lain: Harimau di Sumatera, Orang Utan di Kalimantan, Anoa di Sulawesi, burung Cenderawasih di Papua, dan masih banyak lagi. Demikian pula, cara orang Indonesia memotong hewan untuk dikonsumsi sering kalitidak mempertimbangkan penderitaan dan rasa sakit animalitas. Perlakuan semacam itu mencerminkan kurangnya pertimbangan moral dalam bersikap terhadap animalitas. Padahal, baik filsafat maupun teologi meyakini bahwa hewan/binatang memiliki nilai-nilai bawaan yang perlu dihargai dan menjadi standar moral animalitas.Menggunakan konsep etika-teologis bahwa manusia diciptakan sebagai citra Allah, yang bermakna bahwa mereka tidak hanya diperlengkapi dengan perasaan tetapi juga dengan intelektualitas yang memungkinkan mereka memiliki kapasitas moral, artikel ini menunjuk kepada tanggung jawab moral manusia terhadap lingkungan sekelilingnya, khususnya dunia animalitas.Meskipun mengonsumsi binatang barangkali dapat dianggap sebagai bagian dari tata ciptaan dan daur alam, binatang memiliki hak untuk menikmati kebebasan dan kesejahteraan selama mereka hidup dan harus dihindarkan dari penderitaan. Dalam pengertian demikian kehidupan dan kematian harus diterima secara seimbang. Kesimpulannya, dalam hubungan dengan animalitas, manusia harus menunjukkan sikap moral menghargai, mengasihi, adil, dan mengendalikan diri. Kepedulian dari etika animalitas adalah keberlanjutan kehidupan yang damai dan sejahtera bagi seluruh ciptaan di planet bumi ini.